2001
DOI: 10.1002/jcb.1193
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of endogenous regucalcin in the enhancement of nuclear deoxyribonuleic acid synthesis with proliferation of cloned rat hepatoma cells (H4‐II‐E)

Abstract: The role of endogenous regucalcin in the regulation of deoxyribonuleic acid (DNA) synthesis in the nuclei of the cloned rat hepatoma cells (H4-II-E) with proliferative cells was investigated. Cells were cultured for 6-96 h in a alpha-minimum essential medium (alpha-MEM) containing fetal bovine serum (FBS; 1 or 10%). Cell number was significantly increased between 24 and 96 h after culture with 10% FBS; cell proliferation was markedly stimulated by culture with 10% FBS as compared with that of 1% FBS. In vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
(43 reference statements)
2
23
0
Order By: Relevance
“…We think that the use of different fixation protocols may be causing this histological artifact. RGN immunostaining is visible in cytoplasm as well as in nucleus, which is in accordance with reports showing that RGN is able to translocate to the nucleus regulating DNA synthesis and gene expression (Inagaki & Yamaguchi 2001, Tsurusaki & Yamaguchi 2004, Maia et al 2009). This is the first report describing RGN expression and localization in testis of any vertebrate.…”
Section: Discussionsupporting
confidence: 91%
“…We think that the use of different fixation protocols may be causing this histological artifact. RGN immunostaining is visible in cytoplasm as well as in nucleus, which is in accordance with reports showing that RGN is able to translocate to the nucleus regulating DNA synthesis and gene expression (Inagaki & Yamaguchi 2001, Tsurusaki & Yamaguchi 2004, Maia et al 2009). This is the first report describing RGN expression and localization in testis of any vertebrate.…”
Section: Discussionsupporting
confidence: 91%
“…Endogenous regucalcin has been shown to have a suppressive effect on protein phosphatase, protein kinase, and DNA synthesis activities in proliferative H4-II-E cells following stimulation with FBS , 2001a, 2001b. Regucalcin may play a suppressive role for overexpression of cell proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…This cell may be a tool to study a role of regucalcin in the regulation of cell proliferation. More recently, it has been shown that regucalcin can inhibit protein kinase and protein phosphatase activities which are raised with a proliferation of hepatoma H4-II-E cells Yamaguchi, 2000, 2001a], and that regucalcin has an inhibitory effect on nuclear DNA synthesis in the proliferation of H4-II-E [Inagaki and Yamaguchi, 2001b]. Endogenous regucalcin may have a suppressive effect on proliferation of the cloned rat hepatoma cells.…”
mentioning
confidence: 98%
“…Regucalcin has also been shown to inhibit DNA synthesis in the nuclei of cloned rat hepatoma cells with proliferation after serum stimulation [Inagaki and Yamaguchi, 2001b]. Regucalcin may play a suppressive role in the proliferation of liver cells, because of regulating overexpression of cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Regucalcin can inhibit protein kinase [Inagaki and Yamaguchi, 2001a] and protein tyrosine phosphatase [Inagaki and Yamaguchi, 2000] activities which are increased in the proliferation of the cloned rat hepatoma cells cultured with fetal bovine serum. More recently, it has been demonstrated that endogenous regucalcin has an inhibitory effect on DNA synthesis in the nuclei of cloned rat hepatoma cells cultured with serum stimulation [Inagaki and Yamaguchi, 2001b]. Regucalcin may play an inhibitory role in the signaling pathway, which is related to protein kinase and protein phosphatases in proliferative cells, suggesting a suppressive role of regucalcin in cell proliferation.…”
mentioning
confidence: 98%